Inter-season training effects on cardiovascular health in American-style football players - Amir Hodzic; Patrick Gendron; Emmanuelle Baron; Amélie Éthier; Odile Bonnefous; Eric Saloux; Paul Milliez; Hervé Normand; François Tournoux (BMC, 2024)
Abstract Background Recent studies on American-style football (ASF) athletes raised questions about the impact of training on the cardiovascular phenotype, particularly among linemen players who engage mostly in static exercise during competition and who exhibit concentric cardiac remodeling, often considered maladaptive. We aimed to examine the cardiovascular adaptation to the inter-season mixed-team training program among ASF players. Methods A prospective, longitudinal, cohort study was conducted among competitive male ASF players from the University of Montreal before and after an inter-season training, which lasted 7 months. This program includes, for all players, combined dynamic and static exercises. Clinical and echocardiographic examinations were performed at both steps. Left atrial (LA) and ventricular (LV) morphological and functional changes were assessed using a multiparametric echocardiographic approach (2D and 3D-echo, Doppler, and speckle tracking). Two-way ANOVA was performed to analyze the impacts of time and field position (linemen versus non-linemen). Results Fifty-nine players (20 linemen and 39 non-linemen) were included. At baseline, linemen had higher blood pressure (65% were prehypertensive and 10% were hypertensive), thicker LV walls, lower LV systolic and diastolic functions, lower LA-reservoir and conduit functions than non-linemen. After training, linemen significantly reduced weight (Δ-3.4%, P < 0.001) and systolic blood pressure (Δ-4.5%, P < 0.001), whereas non-linemen maintained their weight and significantly increased their systolic (Δ+4.2%, P = 0.037) and diastolic (Δ+16%, P < 0.001) blood pressure ). Mixed training was associated with significant increases in 2D-LA volume (P < 0.001), 3D-LV end-diastolic volume (P < 0.001), 3D-LV mass (P < 0.001), and an improvement in LV systolic function, independently of the field position. Non-linemen remodeled their LV in a more concentric fashion and showed reductions in LV diastolic and LA reservoir functions. Conclusions Our study underscored the influence of field position on cardiovascular adaptation among university-level ASF players, and emphasized the potential of inter-season training to modulate cardiovascular risk factors, particularly among linemen.